Együttélés vagy asszimiláció? : az Erdélyi Párt viszonya az etnikai kisebbségekkel Észak-Erdélyben 1940 és 1944 között - Murádin, János Kristóf (Közép-Európai Közlemények, 2016)
The study deals with the problem of ethnic relations in Northern Transylvania after the Second Vienna Arbitration, when Hungarians became a majority and Romanians became a minority in the region, offering an overview of the problem from the political perspective. The study concentrates on the analysis of the minority politics of the Erdélyi Párt [`Transylvanian Party`], the most important party of the Transylvanians at that time, with special focus on its basic conception regarding ethnic problems in Transylvania. It presents the foundation of the Transylvanian Party, its representation in the Hungarian Parliament and its relations with the government concerning the minority issue. The study tries to give an overview on the politics of the Transylvanian Party regarding the minorities in Northern Transylvania: Romanians, Germans and Jews. It presents the successes and the failures obtained by the party in this matter in some very important aspects. Finally the decline of the Transylvanian Party and its political heritage are presented. The source material of the study consists of archival data, publications of the Transylvanian Party, special books, studies and publications in the contemporary press.